HUBUNGAN KARAKTERISTIK INDIVIDU DENGAN KINERJA PERAWAT DI RUANG RAWAT INAP PENYAKIT DALAM RSUD DATOE BINANGKANG KABUPATEN BOLAANG MONGONDOW - Kumajas, Fisella Wilfin; Warouw, Herman; Bawotong, Jeavery (JURNAL KEPERAWATAN, 2014)
Abstract: Nurse performance is an ability or learning that has been received for completing nursing education programs to provide services and are responsible for health improvement, disease prevention and patient care. Nurse performances can be affected by the individual characteristic of nurses themselves. The purpose of this study was to determine the correlation of the characteristic of individuals with the performance of nurses in the inpatient room RSUD Datoe Binangkang Bolaang Mongondow. The design of this study using analytic surveywith cross sectional approach. The population are all nurses who work in the inpatient room RSUD Datoe Binangkang Bolaang Mongondow and the sample using total sampling. The results of this study showed a significant correlation of each individual characteristics such as age, education, length of employment, and marital status with the performance of nurses. Conclusions, there is a correlation between characteristics of individuals with the performance of nurses in the inpatient room RSUD Datoe Binangkang Bolaang Mongondow. Suggestions for the hospital to be able to pay attention to the quality of performance of nurses. Keywords: individual characteristics, the performance of nurses Abstrak: Kinerja perawat merupakan aplikasi kemampuan atau pembelajaran yang telah diterima selama menyelesaikan program pendidikan keperawatan untuk memberikan pelayanan dan bertanggung jawab dalam peningkatan kesehatan, dan pencegahan penyakit serta pelayanan terhadap pasien. Kinerja perawat dapat dipengaruhi oleh karakteristik individu dari perawat itu sendiri. Tujuan Penelitian ini adalah untuk mengetahui hubungan karakteristik individu dengan kinerja perawat di ruang rawat inap penyakit dalam RSUD Datoe Binangkang Kabupaten Bolaang Mongondow. Desain penelitian adalah survey analitik dengan pendekatan cross sectional. Sampel penelitian menggunakan total sampling. Hasil penelitian ini menunjukan terdapat hubungan yang signifikan dari masing-masing karakteristik individu yaitu umur, pendidikan, masa kerja, dan status pernikahan dengan kinerja perawat. Kesimpulan ada hubungan antara karakteristik individu dengan kinerja perawat di ruang rawat inap penyakit dalam RSUD Datoe Binangkang Kabupaten Bolaang Mongondow. Saran Bagi pihak rumah sakit untuk dapat memperhatikan kualitas kinerja perawat yang ada. Kata kunci: karakteristik individu, kinerja perawat